PROBLEM ENCOUNTERED IN ORAL PRESENTATION SKILLS OF THE STUDENTS AT GRADUATE PROGRAM - Sangkala, Ismail; Hermawan, Heri; Usman, Fitriani; L.T, Abdullayeva (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This study investigates the difficulties encountered by English Education Program graduate students at State University of Makassar when delivering academic oral presentations. The research explores these difficulties from two perspectives: the students' self-reported experiences and how these difficulties are reflected in the written aspects of the presentations. The goal of the research is twofold: to identify the difficulties that hinder students' successful presentations and to develop solutions to improve their oral presentation skills. By understanding the challenges faced by students, educators can develop more effective teaching strategies to address these difficulties. The findings of this research are expected to benefit both English educators and students. Educators will gain insights into the specific challenges faced by their students during academic oral presentations. This knowledge will allow them to tailor their instruction to better prepare students for these presentations. Students will benefit from the development of improved teaching strategies that target their specific areas of difficulty. The research design employs a mixed-methods approach, combining quantitative and qualitative data collection methods. Data will be collected through student surveys, interviews, and analysis of written presentation materials. The surveys will gather data on the students' self-reported difficulties during oral presentations. The interviews will provide a deeper understanding of the students' experiences and perspectives. Finally, analysis of the written presentation materials will allow researchers to examine how these difficulties manifest in the written aspects of the presentations. This study contributes to the existing body of research on the challenges faced by EFL learners in academic settings. By focusing specifically on the difficulties encountered during oral presentations, the research provides valuable insights for educators who are seeking to improve the oral communication skills of their students. The findings of this research can be applied to English language programs at universities around the world, ultimately improving the quality of academic oral presentations delivered by EFL students.